Debate Pedagogy in Semi-Military Law Enforcement Classrooms: A Case Study of English-Speaking Fluency - Gatot Hadi Waluyo; Urip Sulistiyo; Mukhlash Abrar; Bunga Ayu Wulandari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study examines how debate pedagogy supports the development of English-speaking fluency among third-year cadets in a semi-military law enforcement institution. Guided by an interpretivist paradigm, it adopts a qualitative, single-site case study design focused on the integration of British Parliamentary debates into the English curriculum. Data were generated through semi-structured interviews, focus group discussions, classroom observation of debate sessions, and document analysis involving 36 purposively selected participants (34 high-proficiency cadets and 2 English lecturers). Data were coded and analyzed in NVivo 15 using Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing/verification. The analysis yielded six interrelated thematic advantages of debate for speaking development: training spontaneous yet structured speaking; refining grammar and pronunciation; expanding topic-relevant vocabulary; strengthening logical argumentation; building confidence in English public speaking; and fostering critical thinking, research skills, teamwork, and active listening. These findings indicate that debate-based instruction effectively enhances cadets’ communicative competence and key soft skills when supported by consistent practice, peer collaboration, and constructive lecturer feedback. The study positions debate as a viable instructional strategy for semi-military academies and offers implications for curriculum design that integrates language development with preparation for contemporary, globally oriented law enforcement roles.